Bilateral Single-session PCNL with Minimally Invasive Technique in Pediatric Nephrolithiasis - Wang, Xiaochuan; Zhao, Youquan; Ji, Zhengguo; Yang, Peiqian; Li, Jun; Tian, Ye (Urology Journal, 2024)
Purpose: To assess outcomes of bilateral single-session percutaneous nephrolithotomy (PCNL) with minimally invasive techniques in pediatric population. Materials and Methods: From August 2015 to July 2021, 45 children (including 12 infants) were treated with bilateral single-session PCNL, which included miniPCNL (12-16-Fr) and Microperc (4.8-Fr). Patient, stone and operation-related characteristics, stone-free rate (SFR) and complication rate (CR) were compared using ANOVA. Independent predictors were determined using multivariate linear regression. Results: The mean stone burden was 3.2 cm in sum diameter for both kidneys. For bilateral kidneys, the mean operative time was 61.6min and SFR was 93.3%; CR was 53.3%, of which complications of Clavien grade 1 and 2 accounted for 46.7%. Bilateral Microperc, bilateral miniPCNL and Microperc plus miniPCNL was performed in 19, 14 and 12 children respectively. Both irrigation volume and postoperative stay were less in groups with Microperc. Both SFRs and CRs were satisfactory for the three groups. Self-limiting hematuria represented the most common complication of all cases (33.3%), especially in groups with miniPCNL. The stone burden was the only independent predictor for operative time (P < .001) and the postoperative complication (P = .008). Children with older age (P = .009), higher body mass index (P = .016) or a higher stone burden (P < .001) received larger irrigated fluid volume. Microperc was associated with less irrigated fluid volume (P = .001). Children with Clavien grade 3 complications (P = .004) spent prolonged postoperative hospital stay. Conclusion: With favourable SFR and acceptable CR, bilateral single-session PCNL with minimally invasive techniques might be an effective and safe procedure for pediatric nephrolithiasis.